ENTREPRENEURIAL INITIATIVE AS A FACTOR OF BUSINESS DEVELOPMENT IN THE REGION - Yemets , O.I. (The actual problems of regional economy development, 2022)
The topic of the article is "Entrepreneurial initiative as a factor in business development in the region." The aim of the article is to analyze the state of business development in the region, to identify factors hindering business recovery, to analyze examples of entrepreneurial initiatives in the region - Pizza Veterano, to create shelters, to systematize factors influencing business development in war, to identify military business needs time. In solving the tasks we used a number of research methods: analysis, synthesis and comparison of the peculiarities of business development, taking into account the regional context. The implementation of entrepreneurial initiatives requires the interaction of all stakeholders: businessmen, government officials, consumers. Only mutually beneficial cooperation can be a successful platform for the implementation of business ideas. The directions of business development change in the light of military events, which determine the development trends of the regions through the safe operation of economic entities. It should be noted that the main generator of entrepreneurial initiatives are entrepreneurs, so we analyzed the definition of the term "entrepreneur" by individual authors, supplemented and proposed their own interpretation. An entrepreneur is a creative person who has an initiative that aims to make the most efficient use of resources involved in business (material, labor, financial, intellectual, informational, etc.) and is willing to take risks to organize the production and sale of goods or services needed by society to meet consumer needs. achieving one's own goal - making a profit.A turbulent environment forces you to produce new ideas to support business and save profits. A striking example of entrepreneurial initiatives in the region is the opening of the pizzeria Pizza Veterano, where at least half of the staff must be participants in hostilities. This makes it possible not only to make a profit but also to support the military returning from the war. In order to seek security, when moving people from one region to another, entrepreneurial initiatives involve the creation of shelters - places for temporary stay of persons. It should be noted that the emergence of new business ideas can not be programmed, but it will come when looking for or nurturing. Therefore, entrepreneurial initiative is a determining factor in business development through the use of entrepreneurial qualities to implement new ideas. The scientific novelty is that for the first time entrepreneurial initiatives as a factor of business development in the region under martial law are analyzed. Conclusions and recommendations are of practical significance at the regional level: by identifying creative ideas, it is possible to choose the best initiative, improve business development in the region and create security conditions.